Kajian Alkitab Terhadap Fenomena Ibadah Metaverse - Tjutjun Setiawan; Andreas Joswanto; Tan Lie Lie; Simon Simon (JURNAL LUXNOS, 2022)
Abstract: Metaverse offered a virtual world where each member could interact with one another without face-to-face. Metaverse digital technology has drawn the churches’ interest to utilize it as an option for virtual worship. The existence of metaverse in churches has gradually led to less interaction among believers. Was it true that metaverse made the church ministry easier? What does the Bible say about the metaverse? This research used a literature study in which the function of the church was studied and how it related to the metaverse, a virtual space device. The conclusion is that the digital technology of the metaverse could not always be used in Christian worship. Biblical facts assign the believers' meetings (face-to-face) as an option and priority in communion. The Bible does not reject digital developments but requires believers and church leaders to be critical and wise in facing technological developments to improve the ministry and not to take people away from God and fellow believers because of technological devices. Abstrak: Metaverse menyajikan sebuah dunia virtual di mana setiap anggota dapat saling berinteraksi tanpa harus melakukan tatap muka secara langsung. Teknologi digital metaverse sudah mulai diminati gereja untuk digunakan sebagai opsi dalam melakukan ibadah virtual. Kehadiran metaverse dalam gereja secara perlahan menyebabkan berkurangnya interaksi bagi sesama orang percaya. Benarkah metaverse memudahkan pelayanan gereja? Bagaimana kajian Alkitab terhadap metaverse? Penelitian ini menggunakan metode studi pustaka di mana fungsi gereja dikaji dan bagaimana relevansinya dengan perangkat ruang virtual metaverse. Kesimpulan yang didapat bahwa tidak selalu teknologi digital metaverse dapat dipergunakan dalam hal ibadah Kristiani. Fakta Alkitab menempatkan pertemuan-pertemuan orang percaya (tatap muka) sebagai opsi dan prioritas dalam suatu persekutuan. Alkitab tidak menolak perkembangan digital, namun menuntut orang percaya dan pimpinan gereja untuk bersikap kristis dan bijak dalam menghadapi perkembangan teknologi agar dapat memajukan pelayanan, bukan sebaliknya membawa manusia menjauh dari Allah dan sesama karena perangkat teknologi.